The Seesaw Self: Possessions, Identity (De)activation, and Task Performance. (October 2018) - Chung, Jaeyeon; Johar, Gita V.
Research has shown that possessions have the power to change consumers' self-construal and activate different aspects of the self. Building on this literature, the authors suggest that the salience of product ownership not only activates the product-related self but also simultaneously deactivates product-unrelated selves, resulting in impaired performance on tasks unrelated to the activated self. In five experiments, we first elicit feelings of ownership over a product (e.g., a calculator) to activate a product-related identity (e.g., the math self). Participants then engage in a task that is labeled as being a product-related task (e.g., a math task) or a product-unrelated task (e.g., a visual task). Although the task is the same, participants in the ownership condition perform worse on a task labeled as product-unrelated than those in the baseline condition do. Support for the underlying identity activation process comes from the finding that performance impairment is more likely to hold under conditions of low self-concept clarity, in which identity is malleable. The authors discuss the theoretical and practical implications of this finding.